Urgensi Lisensi Personil PKP-PK Dalam Penerapan Quality Management System - Anggah Prayugo Salim; Muhammad Rizky Syahputra Harahap; M. Rizqi; Yanuar Imam Yoga; Oke Hendra (Langit Biru: Jurnal Ilmiah Aviasi, 2021)
The study was made to improve the quality management system at airport H. Asan Sampit samples for Airport Rescue And Fire Fighter (ARFF). Where every Airport Rescue and Fire Fighter (ARFF) on duty is required to have a suitable license from the directorate general of air transport. The research methods used are qualitative methods that go into data collection and go directly into the field during operation just at h. sampits and interview Airport Rescue and Fire Fighter (ARFF). To improve the quality of Airport Rescue and Fire Fighter personnel (ARFF) in the airport h. stamps of both skills and capabilities so all aircraft in the airport are expected to have licenses in accordance with the regulations of the directorate general of air transport.